The Vintage book of feminism : the essential writings of the contemporary women's movement - Schneir, Miriam (Vintage, 1995)
Starting with the works of Simone de Beauvoir, Doris Lessing and Betty Friedan, this anthology charts the development of the women's movement since World War II. An introduction to each selection is introduced with a commentary by Mirian Schneir that provides interpretation and historical context.